Kajian hipersemiotika terhadap Rozy sebagai virtual influencer Instagram - Nugraha, Nugraha; Saidi, Acep Iwan (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2022)
This study examines Rozy, the first virtual influencer in South Korea produced by Sidus Studio X. Rozy has @rozy.gram as her Instagram social media account which was created on August 19th, 2020. This 22 years old woman is a virtual human representation on Instagram account. Within three months of the account had been released, she had 13,000 followers. Until now, the number has grown to more than 126,000 followers. It makes some advertisings use Rozy as the virtual influencer carries out the role as a marketing strategy. Rozy's Instagram content features four themes, such as fashion, traveling, environment, and daily activities. This study aims to explore the hypersemiotic hierarchy of Rozy's on @rozy.gram account. This study uses a hypersemiotic approach to understand meaning outside of reality. The researchers use descriptive qualitative method to examine the meaning of the signs system. In Rozy's world as a virtual influencer, there are engineering of realities that transcend boundaries by using information and communication technologies. Rozy lives in a reality that are detached from the truth of reality. Through hypersemiotic analysis, it shows that the virtual influencer Rozy is able to trick the human mind and blur the boundaries of reality between real and fake, natural and artificial, and real and unreal. The audiences of Instagram need to be rational, skeptical, and critical in responding to virtual influencers.